KARAKTERISASI SQUAMOUS CELL CARCINOMA PADA RAHANG BAWAH DENGAN METODE PENGENALAN POLA PADA CITRA RADIOGRAF PANORAMIK DIGITAL - Sri Lestari; Rini Widyaningrum (Teknoin, 2016)
Tumour is a pathologic condition that frequently occur in the jaws. Diagnosis is an important process to determine the type of tumour for the patient, especially malignant tumour. A precise and correct diagnosis and supported by a precise treatment planning will support the recovery and a better life expectation for the patient. One of the imaging techniques that commonly used is panoramic radiography. As the objective of this research is to acquire a pattern recognition method on the panoramic radiograph for type of tumour detection in the jaws. The image processing method that applied involve histogram equalization, edge detection, and binary image. The processing has been done by considering the shape, edge, and the characteristic of the tumour. The result of image processing compared with the interpretation by the dentist as the reference analysis. The analysis of the image processing result were appropriate with the dentist‟s interpretation for the case of malignant tumour. As the case of malignant tumour that has been observed was squamous cell carcinoma. The result of pattern recognition on the case of malignant tumour showed unobvious edges, the content of the lesion has radiopaque and radiolucency composition, and the defect of mandibular cortical that can be seen obviously.